cMyBP-C in hypertrophic cardiomyopathy: gene therapy and small-molecule innovations - Wood, Patrick T.; Seffrood, Morgan M.; Colson, Brett A.; Stelzer, Julian E. (Frontiers in Cardiovascular Medicine, 2025)
Hypertrophic cardiomyopathy (HCM) is a genetic disorder in the heart caused by variants in sarcomeric proteins that disrupt myocardial function, leading to hypercontractility, hypertrophy, and fibrosis. Optimal cardiac function relies on the precise coordination of thin and thick filament proteins that control the timing, magnitude of cellular force generation and relaxation, and in vivo systolic and diastolic function. Sarcomeric proteins, such as cardiac myosin binding protein C (cMyBP-C) play a crucial role in myocardial contractile function by modulating actomyosin interactions. Genetic variants in cMyBP-C are a frequent cause of HCM, highlighting its importance in cardiac health. This review explores the molecular mechanisms underpinning HCM and the rapidly advancing field of HCM translational research, including gene therapy and small-molecule interventions targeting sarcomere function. We will highlight novel approaches, including gene therapy using recombinant AAV vectors and small-molecule drugs targeting sarcomere function.